The Role of Ageing and Parenchymal Senescence on Macrophage Function and Fibrosis - Campbell, Ross A.; Docherty, Marie-Helena; Ferenbach, David A.; Mylonas, Katie J. (Frontiers in Immunology, 2021)
In this review, we examine senescent cells and the overlap between the direct biological impact of senescence and the indirect impact senescence has via its effects other cell types, particularly the macrophage. The canonical roles of macrophages in cell clearance and in other physiological functions are discussed with reference to their functions in diseases of the kidney and other organs. We also explore the translational potential of different approaches based around the macrophage in future interventions to target senescent cells, with the goal of preventing or reversing pathologies driven or contributed to in part by senescent cell load in vivo.